Laser Treatment in Nail Disorders: A Comprehensive Review - Byalakere Shivanna Chandrashekar; Chandu Madura; Chaitra Shenoy; Abhijna Chandar; Mysore Seshadri Roopa; Nakka Lakshmi Narayana (Indian Dermatology Online Journal)
Background: Laser therapy has emerged as an innovative approach for managing various nail conditions, offering precise targeting, minimal invasiveness, and favorable safety profiles. This review analyzes the literature on laser therapy for nail indications, encompassing onychomycosis, nail psoriasis, nail warts, ingrown toenails, onychodystrophy, nail pigmentation disorders, and nail tumors. Methods: PubMed and Google Scholar databases were searched to identify articles on laser therapy using specific key terms related to nail conditions (e.g., onychomycosis, nail psoriasis). Relevant articles were shortlisted based on laser treatment in nail disorders, its mechanisms of action, research outcomes, and clinical applications. Results: Nd:YAG or CO2 lasers showed efficacy in onychomycosis by targeting fungal cells. Studies suggest that laser treatments offer comparable results to traditional therapies, often enhancing outcomes when combined with topical agents such as calcipotriol/betamethasone in nail psoriasis. For nail warts, ingrown toenails, onychodystrophy, and nail pigmentation disorders, lasers provide alternative or adjunctive therapies, achieving positive outcomes lesion clearance and symptom improvement. Conclusion: This review underscores the transformative potential of laser therapy in nail disorder management, providing clinicians with innovative treatment alternatives. Nevertheless, further studies are needed to refine protocols, evaluate long-term outcomes and explore its application in specific conditions such as nail tumors.